HP26: Electrophysiological properties of electrical brain stimulations and their impact on neuronal activity during stereoelectroencephalography in epilepsy. (March 2022) - Calvel, A.; Barbeau, E.; Sol, J.C.; Lotterie, J.A.; Guines, K.; Denuelle, M.; Bergaud, C.; Ali, M.; Valton, L.; Curot, J.
Abstract : Intracranial electrical brain stimulations (EBS) are used during stereoelectroencephalography (SEEG) to delineate the epileptogenic zone and to do functional mapping before a surgery. However, current EBS protocols are empirical and limited (with only 2 frequencies, 1 or 50 Hz, whatever the brain area), with a low yield of clinically relevant effects. EBS parameters are not optimal. Moreover, the direct impact of EBS on neuronal activity has seldom been explored and is still a conundrum. Very little is known about the modification of electrical parameters in humans. In this study, we aim to better characterize the electrophysiological properties of EBS delivered during SEEG. While this is an essential basis for understanding the effects of EBS on neural activity at multiple scales simultaneously, little information is available in the literature. To achieve this, we use a novel EBS protocol which includes routine clinical EBS (1 and 50 Hz) and novel EBS frequencies adapted to the brain location. We also conduct multiscale analyses using a novel hybrid intracranial electrode (combining microwires and macroelectrodes), to analyse multiscale (local field potentials, single neuron) changes induced by these EBS. We perform different physical measurements of the delivered current. We have included 14 patients until now, and collected more than 1000 EBS. We determined the total charge, the charge density, the electrodes impedance, the energy delivered and the volume of tissue activated during each type of EBS to better characterize them. We afford preliminary data on their impact on the neuronal dynamics at different scales.